2016
DOI: 10.1002/srin.201600053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Silicon on Desulfurization of Al-Killed Steel by CaO-Al2O3Slag Contained FeO and MnO

Abstract: Industry trials of slag-washing desulfurization in LD tapping process are performed to study the influence of silicon on desulfurization of Al-killed steel using CaO-Al 2 O 3 slag contained FeO and MnO. Influence of silicon on desulfurization is found to be great, while the influences of aluminum and manganese on desulfurization are negligible. Oxygen activity at slag-steel interface together with the (FeO þ MnO) content in slag, decreased with the rise of silicon content, which is considered as the main reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, (FeO + MnO) content can be also controlled in the range from 0.5 to 1% for heats 3–4 without LF refining when silicon content in steel is high, which has been clarified in the previous study. 10 Thus, the influence of (FeO + MnO) content in slag on T.O content is negligible in this study.…”
Section: Resultsmentioning
confidence: 68%
“…However, (FeO + MnO) content can be also controlled in the range from 0.5 to 1% for heats 3–4 without LF refining when silicon content in steel is high, which has been clarified in the previous study. 10 Thus, the influence of (FeO + MnO) content in slag on T.O content is negligible in this study.…”
Section: Resultsmentioning
confidence: 68%
“…increases non-linearly with basicity, from 0.84 to 6.45, as Figure 8A shown. Xu et al (2016) conducted slag-washing trials in LD tapping process to study the effects of silicon on the desulfurization of Al-killed steel using CaO-Al 2 O 3 slag which contained FeO and MnO. Measured oxygen activity at slag-steel reaction is reduced more sharply by increasing the silicon content than that by increasing the aluminum content.…”
Section: Resultsmentioning
confidence: 99%
“…[17,18] The addition of deoxidizers such as Mn, Si, and Al can affect the desulfurization, which largely determines the inclusion characteristic in the steel. Xu et al [19,20] found that silicon in steel liquid can change the composition of the slag to improve the desulfurization ability. Moreover, deoxidizers such as Al, Si, and Mn may also affect the composition of the steel liquid due to interface reactions between slag and steel.…”
Section: Introductionmentioning
confidence: 99%